2014
DOI: 10.1080/1357650x.2014.961472
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for right-hand feeding biases in a left-handed population

Abstract: We have recently shown that actions with similar kinematic requirements, but different end-state goals may be supported by distinct neural networks. Specifically, we demonstrated that when right-handed individuals reach-to-grasp food items with intent to eat, they produce smaller maximum grip apertures (MGAs) than when they grasp the same item with intent to place it in a location near the mouth. This effect was restricted to right-handed movements; left-handed movements showed no difference between tasks. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
(70 reference statements)
1
14
0
Order By: Relevance
“…This result aligns with a previous report in children that showed increased rates of right-hand use for grasping food vs. blocks (Sacrey et al, 2013 ). The result from the present study also reinforces the idea that grasp-to-eat actions might be at the origin of population level right-handedness (Flindall and Gonzalez, 2013 ; Flindall et al, 2014 ). These investigations of hand kinematics have shown evidence that the grasp-to-eat action executed with the right—but not the left-hand elicits smaller grip apertures during the hand pre-shaping phase of the grasp when compared to other grasping movements.…”
Section: Experiments Onesupporting
confidence: 89%
See 1 more Smart Citation
“…This result aligns with a previous report in children that showed increased rates of right-hand use for grasping food vs. blocks (Sacrey et al, 2013 ). The result from the present study also reinforces the idea that grasp-to-eat actions might be at the origin of population level right-handedness (Flindall and Gonzalez, 2013 ; Flindall et al, 2014 ). These investigations of hand kinematics have shown evidence that the grasp-to-eat action executed with the right—but not the left-hand elicits smaller grip apertures during the hand pre-shaping phase of the grasp when compared to other grasping movements.…”
Section: Experiments Onesupporting
confidence: 89%
“…This presumption is supported by findings from Sacrey et al ( 2013 ), who found that children develop a right-hand preference for grasp-to-eat tasks several years earlier than they do for grasp-to-build tasks. Furthermore, Flindall and Gonzalez (Flindall and Gonzalez, 2013 , 2014 , submitted; Flindall et al, 2014 ) have found a left-hemisphere/right-hand advantage in the kinematics of grasp-to-eat/hand-to-mouth actions that is absent from grasp-to-place actions. Specifically, when grasping a small food item with intent to eat, participants produce tighter maximum grip apertures during the outgoing movement than when grasping the same item to place it in a receptacle near the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that left-handers represent a very heterogeneous population (Annett, 1970;Bryden & Huszczynski, 2011;Calvert & Bishop, 1998;Flindall, Stone & Gonzalez, 2014;Gonzalez et al, 2007;Judge & Stirling, 2003;Stone et al, 2013;Tapley & Bryden, 1985;Willems, Van der Haegen, Fisher & Francks, 2014;Yahagi & Kasai, 1999). In fact, in the current study left-hand use values ranged from 4% to 96% when vision was available, illustrating the high variability in manual preference of left-handers (compared to right-handers who ranged from 51% to 100%).…”
Section: Discussionmentioning
confidence: 46%
“…Our finding that hand preference for the grasp-to-eat action is a reliable predictor of the proficiency of speech articulation provides support for the speculation that the hand to mouth action, which developed for ingestion, may also subserve vocal communication (Gentilucci et al, 2009; Flindall and Gonzalez, 2013). Moreover, the grasp-to-eat action has been shown to be lateralized to the left hemisphere (Flindall and Gonzalez, 2013, 2014; Flindall et al, 2014). Specifically they have shown a right hand advantage in the kinematics of grasp-to-eat/hand-to-mouth actions that is absent from grasp-to-place actions.…”
Section: Discussionmentioning
confidence: 99%
“…When grasping a small food item with intent to eat, participants produce tighter maximum grip apertures during the outgoing movement than when grasping the same item to place it in a receptacle near the mouth. This task difference in hand pre-shaping is predominantly lateralized to the right hand, regardless of a person's overall hand preference (Flindall and Gonzalez, 2013; Flindall et al, 2014). This evidence provides support for the notion that the lateralized hand-to-mouth system is a good candidate for the neural basis upon which hand preference for praxis (i.e., tool use and gesturing) and eventually language evolved (Flindall and Gonzalez, 2013; for review, see Corballis, 2003; Pulvermuller and Fadiga, 2010).…”
Section: Discussionmentioning
confidence: 99%